Exploring the Burden of Family Caregivers for Dependent Older Persons under Community-Based Long-Term Care in Nakhon Pathom, Thailand - Aungsumalee Pholpark; Samrit Srithamrongsawat (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2026)
In Thailand, community-based long-term care (LTC) for all Thai dependent older persons has been implemented under the Universal Coverage Scheme since 2016. This study aims to investigate the burden experienced by family caregivers looking after dependent older persons under community-based LTC in Nakhon Pathom Province, Thailand. The data were obtained from a questionnaire survey completed by 313 family caregivers benefitting from community-based LTC in Nakhon Pathom Province. The findings show that community-based LTC could partially alleviate the financial burden related to disposable products and medical equipment expenses, but it has not helped much with time-related burden. Additionally, the services were below the standard outlined in the benefit package guidelines, particularly in terms of the duration and frequency of visits. The findings highlight the need to enhance the quality of services and adopt a targeted approach for the distribution of disposable products and medical equipment to reduce the burden on family caregivers, especially those with lower incomes. This study provides lessons from Thailand’s experience that may apply to other developing countries in Asia facing challenges from ageing societies, informing the establishment of similar community-based LTC systems.